Who Tells the Story? Challenging Audiences through Performer Embodiment - Low, U-Wen (Religions, 2023)
Visualising a character in a narrative is a highly individual act; cognitive narratology suggests that individuals may construct character models depending on the information (frames) available to them. However, many of these frames are formed from knowledge defined by positivist historical criticism, meaning that construction tends to follow broadly similar patterns. Performing and therefore embodying a character shifts the role of interpretation from audience to performer; an audience engages with the nuances of each performer’s embodiment of a character in a shared experience of a temporal performance event. This shift of interpretive responsibility to the performer allows them to challenge audiences in ways that an author may not be able to. Embodiment of a character through performance will inevitably challenge readers’ cognitive constructions of the same character to different degrees—for example, gender, ethnicity, bearing, tone, or even action may differ—potentially creating dissonance for audiences. This dissonance may help interpreters to discover their own assumptions about the performed texts, in doing so creating new avenues for interpretation. Such is the promise of performance: by viewing embodied narratives, audiences are challenged to view alternative interpretations and subsequently reconcile differences between their constructions and those of the performers.